Sporadic Land Registration Counseling and Socialization to Provide Legal Certainty in Sindang Jaya Subdistrict - Fitri Wahyuni; Asep Somantri; Sarah Rahmadika; Dini Rizki Rahayu (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service program aims to enhance public understanding and awareness of the importance of sporadic land registration in order to provide legal certainty of land ownership in Sindang Jaya Village. The main problem faced by the community is the lack of knowledge regarding land registration procedures, administrative requirements, and legal benefits, which may lead to land disputes. The method used in this activity is a participatory approach through Participatory Action Research (PAR), including planning, implementation, observation, and reflection stages. The activities were conducted through counseling, socialization, and interactive discussions. The results show a significant improvement in community understanding regarding procedures, requirements, and legal benefits of land registration. Furthermore, the program increased public awareness and encouraged proactive participation in registering land. This activity is proven effective in improving legal awareness and can be used as a reference model for similar community service programs.